Peran Dukungan Suami dan Faktor Lainnya terhadap Pemanfaatan Pelayanan Gizi oleh Ibu Hamil dengan Risiko Kurang Energi Kronis (KEK) - Fauzul Hayat; Nurce Arifiati; Tria Astika Endah Permatasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the factors that cause the behavior of using nutrition services by pregnant women with the risk of KEK at the Nutrition Clinic of the Kasemen Health Center, Serang City. This research method uses cross-sectional research. The results showed that 66.2% of pregnant women at risk of KESK did not take advantage of nutrition services at the nutrition clinic. The behavior of the utilization of nutrition services in pregnant women with the risk of SEZ was most dominantly influenced by support (OR=6.31; 95% CI: 2.633-15.138). In addition, this behavior is influenced by other factors, namely needs (OR = 5.22; 95% CI: 1.608-16.926) and family income (OR = 2.48; 95% CI: 1.061-5.814). In conclusion, pregnant women at risk of CED who do not receive support from their husbands are at risk of 6.31 times more at risk of not using nutrition services than pregnant women with the risk of CED who receive their husband's support. Keywords: Pregnant Women, Nutrition Services, Risk of Chronic Energy Deficiency (KEK)